Forest policy for private forestry : global and regional challenges (CABI, 2003)
This book addresses key issues currently shaping the future of private forestry. The main subjects covered in the 27 chapters include the emergence of a new paradigm for public involvement in private forestry, the challenges of sustainability, forest certification programmes, and country experiences from the Americas, Europe, Asia, and Oceania.